High-Quality Ruddlesden–Popper Perovskite Film Formation for High-Performance Perovskite Solar Cells - Liu, P.; Han, N.; Wang, Wei; Ran, R.; Zhou, W.; Shao, Zongping (WILEY-V C H VERLAG GMBH, 2021)
In the last decade, perovskite solar cells (PSCs) have undergone unprecedented rapid development and become a promising candidate for a new-generation solar cell. Among various PSCs, typical 3D halide perovskite-based PSCs deliver the highest efficiency but they suffer from severe instability, which restricts their practical applications. By contrast, the low-dimensional Ruddlesden–Popper (RP) perovskite-based PSCs have recently raised increasing attention due to their superior stability. Yet, the efficiency of RP perovskite-based PSCs is still far from that of the 3D counterparts owing to the difficulty in fabricating high-quality RP perovskite films. In pursuit of high-efficiency RP perovskite-based PSCs, it is critical to manipulate the film formation process to prepare high-quality RP perovskite films. This review aims to provide comprehensive understanding of the high-quality RP-type perovskite film formation by investigating the influential factors. On this basis, several strategies to improve the RP perovskite film quality are proposed via summarizing the recent progress and efforts on the preparation of high-quality RP perovskite film. This review will provide useful guidelines for a better understanding of the crystallization and phase kinetics during RP perovskite film formation process and the design and development of high-performance RP perovskite-based PSCs, promoting the commercialization of PSC technology.